Modeling of hydro-oceanographic parameters and its possible impact on coral reef cover in Derawan Island waters, East Kalimantan, Indonesia - Adalya, Natasya M. (Springer Science and Business Media Deutschland GmbH, 2022)
Derawan waters in Indonesia have a high number of coral reefs diversity and ranked second after the Raja Ampat Islands in Papua. Unfortunately, the percentage of coral cover in Derawan Island tends to decrease due to various factors, such as hydro-oceanographic dynamics. This study aims to determine the hydro-oceanographic characteristics and their possible impacts on coral reef cover in Derawan waters using remote sensing analysis, field surveys, GIS modeling, and geostatistical analysis. We modeled the hydro-oceanographic parameters, i.e., SST, salinity, sea surface currents, and bathymetry, using the Kriging method in GIS software. We obtained benthic habitats through Sentinel-2 image processing, validated with video-recorded line transects to get the percentage of coral reef cover, coral mortality index, and spatial distribution of corals. The results showed that we could use the Kriging method to produce an accurate and valid model of hydro-oceanographic parameters in Derawan waters. Derawan waters have a wide range of coral reef coverage, with the highest in the West (74.55 percent) and the lowest in the East (28.60 percent). Furthermore, the highest and lowest coral mortality indexes are found in the South and West, respectively. The hydro-oceanographic parameters in Derawan waters are ideal for coral survival, and only salinity, which is extremely good for coral growth, according to Nybakken's theory. A more detailed study is needed to gain a complete description of the dynamics of hydro-oceanography and coral reef ecosystems in Derawan waters so that policymakers can use them to mitigate and conserve marine ecosystems. © 2022, The Author(s), under exclusive licence to Springer Nature Switzerland AG.